Modernizing the Academic Teaching and Research Environment Methodologies and Cases in Business Research (Progress in IS, 2018)
This book constitutes a valuable manual for young and seasoned business researchers alike, and provides a comprehensive summary for the whole research journey. It is a must-read for all researchers who need to understand the basics of business research, from identifying research topics, to planning and organizing the research process, and selecting the most appropriate methodology for the topic at hand. This book also provides insights on how to avoid common pitfalls in business research and outlines the research skills needed to write a fine piece of research. In order to capture the innovative element of research, the book also highlights methods for thinking outside the box. It also stresses the importance of respecting ethics while conducting business research. Lastly, it presents important cases and provides hands-on training for preparing survey tools. Readers looking to master business research won't want to miss out on this unique and insightful book.